Lower uterine segment scar thickness as a predictor of successful vaginal birth after caesarean section at the Federal Medical Centre, Yenagoa: a prospective cohort study - Ikoro, Chima; Omietimi, James Enimi; Kiridi, Enefia Kelvin; Fumudoh, Bassey; Samuel Aigere, Egbaname O.; Oriji, Peter Chibuzor; Mbah, Kanayochukwu Michael; Tekenah, Ebiye Serena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Successful conduct of vaginal birth after caesarean section is dependent on a number of foetal and maternal factors including integrity of the previous caesarean section scar. The objective of this study was to determine the average lower uterine segment (LUS) scar thickness for women being planned for VBAC. Methods: This was a prospective cohort study of pregnant women with one previous caesarean section, who were recruited to undergo transvaginal ultrasound scan in preparation for VBAC at the Federal Medical Centre (FMC) Yenagoa. It was conducted between May, 2018 and September 2019. The women were allocated into three groups A (<2.5mm), B (2.5-3.4 mm) and C (≥3.5 mm) according to the thickness of the LUS scar. Data analysis was done using the statistical product and service solutions version 22.0, p<0.05 was taken as statistically significant. Results: The range of lower uterine segment thickness in the study was 1.5 mm to 6.8 mm (mean 3.89±0.95 mm). With cut-off value of 3.5 mm, the sensitivity for successful VBAC was 78.8%, specificity was 55.4%, PPV was 78.1%, NPV was 62.0% and accuracy was 71%. The rate of uterine defect increased as the lower uterine segment thickness decreased from 3.5 mm (p=0.001). Conclusions: This research has clearly shown that full LUS thickness of ≥3.5 mm at 36 weeks of gestation is associated with an increased chance of successful VBAC while LUS thickness of <3.5 mm is at increased risk of uterine rupture and uterine dehiscence during a Trial of VBAC.